Pengaruh Pengendalian Internal, Ketaatan Aturan Akuntansi Terhadap Akuntabilitas Keuangan dengan Pencegahan Kecurangan (Fraud) sebagai Variabel Intervening pada Travel Haji dan Umrah di Kotamadya Jambi - Mufidah Mufidah; Amilia Paramita Sari (Universitas Batanghari Jambi, 2018)
The purpose of this study is to analyze the influence of internal control, Obedience of accounting rules to financial accountability through fraud prevention as intervening variable at Hajj Umroh Travel in Jambi Municipality. The type of this research is descriptive which is a survey on Hajj and Umroh Travel in Jambi Municipality. Data collection with literature study and field study. The time period used is cross sectional conducted in April - May 2018. The number of respondents is 37 hajj and umroh travel in Jambi Municipality. Data analysis for hypothesis testing using inferential statistic was measured using Partial Least Square (PLS).